Il tempo e il perdono. Una lettura di Rabbia e perdono di Martha Nussbaum - Poli, Edoardo (Filosofia Morale/Moral Philosophy, 2024)
The paper aims to analyze and criticize Martha Nussbaum’s essay Anger and Forgiveness, where the philosopher thematizes the notion of forgiveness. Firstly, I will show how forgiveness is conceived by Nussbaum, then I will discuss her concept according to French theory, focusing on the role of memory and oblivion. Eventually, I will use Levinas’ theory of time to demonstrate how forgiveness implies the time dimension of the future as well as the past.